Dynamics of the polynomial differential systems - Fatima, Feneniche; Salem, Rezaoui Med (Turkish Journal of Computer and Mathematics Education (TURCOMAT), 2023)
In general, there are several free parameters. By using a method introduced in a previous paper, we obtain a sequence of algebraic a proximations to the bifurcationsets,in the parameter space